Relationship between gene responses and symptoms induced by Rice grassy stunt virus - Satoh, Kouji; Yoneyama, Kaori; Kondoh, Hiroaki; Shimizu, Takumi; Sasaya, Takahide; Choi, IL Ryong; Yoneyama, Koichi; Omura, Toshihiro; Kikuchi, Shoshi (Frontiers in Microbiology, 2013)
Rice grassy stunt virus (RGSV) is a serious threat to rice production in Southeast Asia. RGSV is a member of the genus Tenuivirus, and it induces leaf yellowing, stunting, and excess tillering on rice plants. Here we examined gene responses of rice to RGSV infection to gain insight into the gene responses which might be associated with the disease symptoms. The results indicated that 1) many genes related to cell wall synthesis and chlorophyll synthesis were predominantly suppressed by RGSV infection; 2) RGSV infection induced genes associated with tillering process; 3) RGSV activated genes involved in inactivation of gibberellic acid and indole-3-acetic acid ; and 4) the genes for strigolactone signaling were suppressed by RGSV. These results suggest that these gene responses to RGSV infection account for the excess tillering specific to RGSV infection as well as other symptoms by RGSV, such as stunting and leaf chlorosis.